Non-stick layer, preparation method thereof and non-stick appliance comprising non-stick layer

CN119372736APending Publication Date: 2025-01-28WUHAN SUPOR COOKWARE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310927724.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing metal cookware such as magnesium alloy, aluminum alloy, titanium alloy, etc. are prone to sticking to the pot during the cooking process, which affects the user experience.

Method used

Modified by the micro -arc oxidation film, and the pores in the filled filter are used to form a non -stick layer with non -sticky effect. The non -sticky layer includes micro -arc oxide film and silicon oil. Silicon oil is fixed in the membrane through impregnation and baking process to provide a long -lasting non -sticky effect.

Benefits of technology

It is realized during the cooking process, improved the experience of cooking utensils, and maintained a long -lasting durable non -sticky effect through the slow release effect of silicone oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372736A_ABST
    Figure CN119372736A_ABST
Patent Text Reader

Abstract

The inventive concept provides a non-stick layer, a method of making the same, and a non-stick appliance including the non-stick layer. The non-stick layer comprises a micro-arc oxidation film which is formed by a metal material through a micro-arc oxidation technology, and the micro-arc oxidation film is provided with a plurality of pores; and the silicone oil is filled in at least surface layer pores of the micro-arc oxidation film. According to the invention, pores in the micro-arc oxidation film are filled with the silicone oil, so that the micro-arc oxidation film adsorbed with the silicone oil has excellent corrosion resistance and non-stickiness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of non-stick technology, and in particular relates to a non-stick layer formed by using a micro-arc oxidation technology, a preparation method thereof, and a non-stick utensil comprising the non-stick layer. Background Art

[0002] The micro-arc oxidation film has a very high hardness, is not only wear-resistant, but also resistant to high temperatures and corrosion. The micro-arc oxidation process for magnesium alloys, aluminum alloys, and titanium alloys is very mature and has a wide range of applications.

[0003] At present, cookware made of magnesium alloy, aluminum alloy and titanium alloy has been widely used in the kitchen and household fields. It is light and easy to use and is deeply loved by consumers. However, these metals are not corrosion-resistant or easily oxidized and discolored. Therefore, people have carried out micro-arc oxidation treatment on cookware made of these materials to overcome the problem of metal oxidation and discoloration. However, the oxide film of these metals is very easy to stick to food, and it is very easy to stick to the pan during cooking, which makes consumers have a poor user experience. Summary of the invention

[0004] Therefore, it has become an urgent need to modify the micro-arc oxidation film to make it non-sticky in order to improve the consumer experience.

[0005] Based on this, the present invention provides a technology for improving micro-arc oxidation film, through which a non-stick layer with excellent non-stick effect based on the micro-arc oxidation film, a preparation method thereof and a non-stick device including the non-stick layer can be provided.

[0006] According to one aspect of an exemplary embodiment, a non-stick layer includes: a micro-arc oxidation film, which is formed by a metal material using a micro-arc oxidation process, and has a plurality of pores; and silicone oil, which fills at least some of the plurality of pores (for example, fills at least the surface pores of the micro-arc oxidation film).

[0007] The silicone oil may be selected from at least one of methyl silicone oil, dimethyl silicone oil, hydroxy silicone oil, hydrogen silicone oil and polyether-modified silicone oil.

[0008] In terms of weight percentage, the silicone oil may include 20%-30% of low molecular weight silicone oil, 40%-60% of medium molecular weight silicone oil, and 20%-30% of high molecular weight silicone oil, wherein the molecular weight of the low molecular weight silicone oil may be between 500-1000, the molecular weight of the medium molecular weight silicone oil may be between 3000-6000, and the molecular weight of the high molecular weight silicone oil may be between 12000-30000.

[0009] The non-stick layer may further include a sealing layer on the micro-arc oxidation film, and the sealing layer may be formed by using a ceramic coating.

[0010] The thickness of the sealing layer may be in the range of 3 micrometers to 15 micrometers.

[0011] The metal material may include at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium, and titanium alloy.

[0012] According to another aspect of the exemplary embodiment, a method for preparing a non-stick layer includes: forming a micro-arc oxidation film on a substrate using a micro-arc oxidation method; immersing the micro-arc oxidation film in silicone oil or a silicone oil solution so that the silicone oil fills at least some of the multiple pores included in the micro-arc oxidation film (for example, filling at least the surface pores of the micro-arc oxidation film).

[0013] In the immersion step, the micro-arc oxidation film immersed in the silicone oil may be ultrasonically treated using ultrasonic waves.

[0014] After the dipping step, the micro-arc oxidation film may be baked at a temperature of 300° C. to 350° C. for 5 min to 10 min.

[0015] After the dipping step, a sealing layer may be formed on the micro-arc oxidation film by a spraying process using a ceramic coating.

[0016] According to still another aspect of the exemplary embodiment, a non-stick utensil includes: a base; and the non-stick layer as described above, located on the base.

[0017] The thickness of the micro-arc oxidation film is in the range of 14 microns to 40 microns. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] These and / or other features will become more apparent and more easily understood through the following detailed description of embodiments thereof in conjunction with the accompanying drawings, in which:

[0019] Figure 1 is a schematic cross-sectional view of a non-stick utensil according to a first exemplary embodiment;

[0020] Figure 2 is a schematic cross-sectional view of a non-stick utensil according to a second exemplary embodiment;

[0021] Figure 3 is a schematic cross-sectional view of a non-stick utensil according to a third exemplary embodiment;

[0022] Figure 4 is a schematic cross-sectional view of a non-stick utensil according to a fourth exemplary embodiment. DETAILED DESCRIPTION

[0023] The present invention will now be described more fully hereinafter with reference to the accompanying drawings, in which various embodiments are shown. However, the present invention may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the disclosure will be thorough and complete, and will fully convey the scope of the present invention to those skilled in the art. The same reference numerals always refer to the same elements.

[0024] Micro-arc oxidation (MAO) is also known as plasma electrolytic oxidation (PEO). This process mainly relies on the matching and adjustment of electrolyte and electrical parameters. Under the instantaneous high temperature and high pressure generated by arc discharge, a modified ceramic coating mainly composed of matrix metal oxide and supplemented by electrolyte components grows on the surface of valve metals such as aluminum, magnesium, titanium and their alloys. Its anti-corrosion and wear-resistant properties are significantly better than traditional anodized coatings. Therefore, micro-arc oxidation films are often used as anti-corrosion and wear-resistant layers for cookware.

[0025] However, the micro-arc oxidation film has a porous structure, and the pores are prone to adsorb proteins and starches in food during cooking, causing food to stick to the pan. If the pores of the micro-arc oxidation film can be modified to have a hydrophobic effect, and a stable oil film can be formed on its surface during cooking, and the oxidation film layer can continuously store oil, the direct contact between the food and the oxidation film can be isolated, thereby achieving better non-stick properties. Therefore, the present invention provides a non-stick layer including a modified micro-arc oxidation film and a cooker including the non-stick layer, wherein the pores of the micro-arc oxidation film included in the non-stick layer include silicone oil, so that the silicone oil bound in the pores is continuously and slowly released during the use of the utensil (for example, a non-stick cookware), thereby maintaining a long-lasting non-stick effect.

[0026] Now, exemplary embodiments of the present invention will be described hereinafter with reference to the accompanying drawings.

[0027] Figure 1 is a schematic cross-sectional view of a non-stick utensil according to a first exemplary embodiment of the present inventive concept.

[0028] The non-stick utensil according to the exemplary embodiment can be applicable to any scenario requiring non-stick (such as non-stick coating of cooking pots (e.g., frying spoons, rice cooker inner pots) and inner and outer coatings of transportation pipelines, etc.), and can include a substrate 1 and a non-stick layer formed on the substrate 1.

[0029] The substrate 1 is not only used as the main body of the entire non-stick utensil, but also used to form the micro-arc oxidation film 2 included in the non-stick layer to be described below. The micro-arc oxidation film 2 is formed by a micro-arc oxidation process using the metal material of the substrate, that is, the micro-arc oxidation film 2 is an oxide film formed on the surface of the substrate on which the non-stick layer is to be formed under a micro-arc oxidation environment. Therefore, based on the micro-arc oxidation process, the substrate may include at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium and titanium alloy. Therefore, the micro-arc oxidation film 2 formed based on the substrate 1 using the micro-arc oxidation process may be an oxide of aluminum, magnesium, or titanium. However, the exemplary embodiment does not limit the substrate 1 to only include the above-mentioned metal materials, and those skilled in the art may select a suitable metal material as the material of the substrate 1 based on the prior art, but the surface of the substrate 1 needs to include a metal material that can be micro-arc oxidized. That is to say, the substrate 1 can have materials such as stainless steel and iron, and in addition to these materials, the surface of the substrate 1 also needs to include materials for micro-arc oxidation (for example, further including at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium and titanium alloy). In this case, the substrate can have a composite structure in which a metal material for micro-arc oxidation (for example, at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium and titanium alloy) is stacked with other metal materials.

[0030] The non-stick layer is formed on the substrate 1 and may include a micro-arc oxidation film 2 and silicone oil 4 .

[0031] The micro-arc oxidation film 2 is formed on the substrate 1. The micro-arc oxidation film 2 is formed by a micro-arc oxidation process using the substrate 1, and therefore, the micro-arc oxidation film 2 may include an oxide of a surface metal material of the substrate 1. According to an exemplary embodiment, when the substrate 1 includes at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium, and titanium alloy, the micro-arc oxidation film 2 may correspondingly include at least one of aluminum oxide, titanium oxide, and magnesium oxide, but the inventive concept does not limit the material of the micro-arc oxidation film. When other metal materials capable of undergoing a micro-arc oxidation process are selected as the material of the substrate 1, the micro-arc oxidation film 2 may include an oxide of the corresponding metal material.

[0032] The micro-arc oxidation film 2 has a plurality of pores 3 due to the nature of the micro-arc oxidation process, and the silicone oil 4 included in the non-stick layer can be filled in at least some of these pores. For example, the silicone oil 4 can fill at least the surface pores of the micro-arc oxidation film 2, where the term "surface" can refer to the outermost layer (e.g., the uppermost layer) of the micro-arc oxidation film away from the substrate 1 or the layer closest to the outside, and therefore, the term "surface pores" can be understood as the outermost pores of the micro-arc oxidation film away from the substrate 1. However, the exemplary embodiment is not limited thereto. Preferably, as will be described below, when a low molecular weight silicone oil, a medium molecular weight silicone oil and a high molecular weight silicone oil are combined and acted on by agents such as titanates and coupling agents, the silicone oil can be fully filled in almost most or even all of the pores, and the silicone oil 4 filled and combined in the pores 3 can be slowly released during use, thereby maintaining a long-lasting non-stick effect of the non-stick layer.

[0033] According to an exemplary embodiment, silicone oil 4 is bound (e.g., adsorbed, bonded) to pores 3 and provides primary non-stickiness for the non-stick layer. Here, silicone oil 4 may be selected from at least one of methyl silicone oil, dimethyl silicone oil, hydroxy silicone oil, hydrogen silicone oil, and polyether modified silicone oil. In addition, by weight percentage, the silicone oil 4 may include 20%-30% of low molecular weight silicone oil, 40%-60% of medium molecular weight silicone oil, and 20%-30% of high molecular weight silicone oil, and the molecular weight of the low molecular weight silicone oil may be between 500-1000, the molecular weight of the medium molecular weight silicone oil may be between 3000-6000, and the molecular weight of the high molecular weight silicone oil may be between 12000-30000. Here, silicone oil 4 may be prepared by mixing different molecular weights, because: silicone oil with a large molecular weight is more firmly bonded to the sustained-release material and releases more slowly; silicone oil with a small molecular weight has better free mobility, thereby having better non-stickiness; in addition, silicone oil with a medium molecular weight takes into account both free mobility and bonding firmness. Therefore, by combining low molecular weight silicone oil, medium molecular weight silicone oil and high molecular weight silicone oil, the sustained release and non-stick effects can be better exerted.

[0034] In addition, as will be described below, when the micro-arc oxidation film 2 is impregnated with a silicone oil solution, at least part of the pores of the micro-arc oxidation film 2 may also include a solvent (e.g., isopropyl alcohol) in the silicone oil solution, however, due to a subsequent baking process, the solvent can be volatilized and only exist in a small amount in the pores or be completely removed from the pores. The inventive concept is not limited thereto.

[0035] In addition, in order to improve the bonding strength between the silicone oil 4 and the micro-arc oxidation film 2, the pores 3 may further include at least one of a titanate (not shown) and a coupling agent (not shown) as a catalyst in addition to the silicone oil 4. Here, the coupling agent may include a silane coupling agent. However, the exemplary embodiment is not limited thereto, and the coupling agent and / or the coupling agent may be omitted.

[0036] Above, combined Figure 1 The non-stick utensil of the first exemplary embodiment of the present inventive concept is described in detail. Figure 2-Figure 4 Non-stick utensils according to other exemplary embodiments of the present inventive concept will be described in detail.

[0037] Figure 2 is a schematic cross-sectional view of a non-stick utensil according to a second exemplary embodiment.

[0038] Reference Figure 2 , the non-stick utensil according to the second exemplary embodiment of the present inventive concept is different from the reference Figure 1 The non-stick utensil of the first exemplary embodiment described has substantially the same structure, and the only difference is that the non-stick utensil of the second exemplary embodiment further includes a sealing layer 5 .

[0039] According to an exemplary embodiment, the sealing layer 5 is used to further seal the micro-arc oxidation film 2, and may include a ceramic coating. Here, the ceramic coating may be a ceramic coating known in the art. For example, according to an example, a silane substance, an alkaline silica sol, and a non-sticking agent may be formulated into a ceramic coating for sealing according to a general ratio formula. However, the inventive concept does not limit the formula of the ceramic coating.

[0040] In addition, in order to better achieve pore sealing, the pore sealing layer according to the exemplary embodiment may have a thickness of 3 micrometers to 15 micrometers.

[0041] Since the ceramic coating is used as the sealing layer of the micro-arc oxidation film 2, the release of silicone oil in the pores of the micro-arc oxidation film can be further slowed down, thereby further enhancing the non-stick effect.

[0042] Figure 3 is a schematic cross-sectional view of a non-stick utensil according to a third exemplary embodiment.

[0043] Reference Figure 3 , the non-stick utensil according to the third exemplary embodiment of the present inventive concept is different from the reference Figure 2 The non-stick utensil of the second exemplary embodiment described has substantially the same structure, and the only difference therebetween is that the surface of the base 1 of the non-stick utensil of the third exemplary embodiment is surface-treated to have a concavo-convex surface 6 .

[0044] In order to better achieve micro-arc oxidation and make the formed micro-arc oxidation film 2 firmly bonded to the substrate 1, the substrate 1 of the non-stick utensil according to the third exemplary embodiment can have a surface roughness of 3 microns to 15 microns. With such a surface roughness, the roughness and hardness of the substrate 1 can be increased, so that it can have better bonding force and wear resistance. In the case where the substrate 1 has a single-layer structure, the upper surface of the substrate 1 can have a surface roughness of 3 microns to 15 microns, or, when the substrate has a multi-layer structure (not shown), the surface of the uppermost layer of the multi-layer structure can have a surface roughness of 3 microns to 15 microns.

[0045] To realize the concavo-convex surface 6 of the substrate 1, the substrate 1 may be functionalized. Here, the functionalization may include shot peening, embossing, knurling, turning, etching, or die casting. However, the exemplary embodiment is not limited thereto.

[0046] Figure 4 is a schematic cross-sectional view of a non-stick utensil according to a fourth exemplary embodiment.

[0047] Reference Figure 4 , the non-stick utensil according to the fourth exemplary embodiment of the present inventive concept is different from the reference Figure 3 The non-stick utensil of the third exemplary embodiment described has substantially the same structure, the only difference being that the substrate 1 of the non-stick utensil of the fourth exemplary embodiment may have a double-layer structure, which may have the same or different materials, and the surface of the uppermost layer is treated with micro-arc oxidation.

[0048] For example, the substrate 1 of the non-stick utensil according to the fourth exemplary embodiment may include a first layer 1-1 and a second layer 1-2. Here, the first layer 1-1 may be a material known in the art for forming a substrate of a non-stick utensil, such as iron, stainless steel, etc., and the second layer 1-2 needs to be used to form a micro-arc oxidation film 2, so it needs to include a metal material for micro-arc oxidation, for example, including at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium and titanium alloy. However, the exemplary embodiment is not limited thereto. Although Figure 4 The substrate 1 is shown as having a double-layer structure, but those skilled in the art can configure the substrate 1 to have a Figure 1-Figure 3 The single-layer structure shown in the figure, or the substrate 1 is provided with a three-layer or more-layer structure, and in the case of a multi-layer structure, the uppermost layer of the substrate 1 of the multi-layer structure needs to include a metal material capable of micro-arc oxidation.

[0049] Above, the non-stick utensil including the non-stick layer including the micro-arc oxidation film 2 and the silicone oil 4 according to the present invention is described in detail in conjunction with the exemplary embodiments. In the following, the method for manufacturing the non-stick utensil will be described in detail.

[0050] The method for manufacturing a non-stick utensil according to the present invention may include: providing a substrate 1; forming a micro-arc oxidation film 2 using a micro-arc oxidation process; and filling pores 3 in the micro-arc oxidation film 2 with silicone oil.

[0051] According to an exemplary embodiment, the substrate 1 may be a substrate known in the art for making non-stick utensils (e.g., non-stick cookware), and may include a metal material for micro-arc oxidation, for example, including at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium, and titanium alloy. As described above, when the substrate 1 has a multilayer structure, the substrate 1 has a plurality of layers except for the top layer (e.g., Figure 4 1-2) includes a metal material for micro-arc oxidation, and the substrate 1 has, except for the uppermost layer (e.g., Figure 4 1-2) in the other layers (for example, Figure 4 1-1) in the above may include other materials, and the inventive concept is not limited thereto.

[0052] In addition, the base 1 may have an applicable shape. For example, when the non-stick utensil is used for a cooker, the base 1 of the non-stick utensil may have the shape of the cooker and may be formed by stamping or die-casting, however, the exemplary embodiment is not limited thereto.

[0053] After providing the substrate 1, the surface of the substrate 1 may be treated so that the surface of the substrate 1 has a surface roughness of 3 micrometers to 15 micrometers. Here, the surface treatment method of the substrate 1 may include shot peening, embossing, knurling, turning, etching, or a method of engraving a pattern on a mold during die casting. However, the exemplary embodiment is not limited thereto, and the surface treatment step may be omitted.

[0054] After the substrate 1 is prepared, the substrate 1 may be subjected to micro-arc oxidation treatment to form a micro-arc oxidation film 2 on the surface of the substrate 1. According to the present invention, the prepared substrate 1 may be subjected to micro-arc oxidation treatment using a micro-arc oxidation process known in the art, however, the present invention does not limit the micro-arc oxidation treatment process.

[0055] According to a specific example, 5g / L-8g / L of sodium silicate, 1g / L-4g / L of sodium hydroxide, and 1g / L-2g / L of sodium fluoride can be used to prepare an alkaline bath solution. In a constant voltage mode of 300V-600V, a pulse frequency of 500Hz-800Hz and a duty cycle of 10%-30% are set, and micro-arc oxidation of the substrate 1 is performed for 20min-60min.

[0056] After micro-arc oxidation, a micro-arc oxidation film 2 with a thickness of 15 microns to 40 microns can be formed on the surface of the substrate 1 .

[0057] After the micro-arc oxidation film 2 is formed, the substrate 1 on which the micro-arc oxidation film 2 is formed may be immersed in silicone oil or silicone oil solution so that the silicone oil 4 penetrates into the pores 3 of the micro-arc oxidation film 2 .

[0058] According to an exemplary embodiment, the silicone oil 4 can be selected from at least one of methyl silicone oil, dimethyl silicone oil, hydroxy silicone oil, hydrogen silicone oil and polyether modified silicone oil, or a solvent (e.g., isopropanol, butyl acetate, etc.) can be added as needed to prepare a silicone oil solution to adjust the viscosity of the silicone oil. For example, when preparing a silicone oil solution, the silicone oil and the solvent (e.g., isopropanol, butyl acetate, etc.) can be configured into a silicone oil solution in a ratio of 1:2-2:1 by mass percentage.

[0059] In addition, by weight percentage, silicone oil 4 can include 20%-30% low molecular weight silicone oil, 40%-60% medium molecular weight silicone oil, and 20%-30% high molecular weight silicone oil, and the molecular weight of the low molecular weight silicone oil can be between 500-1000, the molecular weight of the medium molecular weight silicone oil can be between 3000-6000, and the molecular weight of the high molecular weight silicone oil can be between 12000-30000. Here, silicone oil 4 can be prepared by mixing different molecular weights, because: large molecular weight silicone oil is more firmly combined with the sustained-release material and releases more slowly; small molecular weight silicone oil has better free mobility and thus has better non-stickiness; in addition, medium molecular weight silicone oil takes into account both free mobility and binding firmness. Therefore, by combining low molecular weight silicone oil, medium molecular weight silicone oil and high molecular weight silicone oil, the sustained-release and non-stick effects can be better exerted.

[0060] Therefore, according to an exemplary embodiment, at least one silicone oil (for example, a single silicone oil including only a single molecular weight, or a mixture of silicone oils including multiple molecular weights) can be used as an immersion liquid to achieve silicone oil impregnation of the micro-arc oxidation film 2, or a silicone oil solution including at least one silicone oil can be used as an immersion liquid to achieve silicone oil impregnation of the micro-arc oxidation film 2.

[0061] In order to achieve the filling of silicone oil into more pores 3, ultrasound can be used to promote impregnation during the impregnation process. Here, the ultrasonic treatment time can be 0.5h-2h. In addition, during the impregnation process, in order to promote the combination of silicone oil 4 and micro-arc oxidation film 2, titanate and / or coupling agent (for example, silane coupling agent) as a catalyst can be added to the impregnation liquid. Here, the amount of titanate and / or coupling agent added can be 0.1%-0.3% of the total weight of silicone oil or silicone oil solution including titanate and / or coupling agent used for impregnation. The addition of titanate and / or coupling agent can promote the filling of silicone oil and the combination with pores. However, exemplary embodiments are not limited to this, and the catalyst can be omitted.

[0062] After impregnation, the impregnation can be removed, then wiped dry, and can be baked at a temperature of 300°C-350°C for 5min-10min to facilitate the curing of the silicone oil. Thus, a non-stick utensil including a substrate 1 and a non-stick layer composed of a micro-arc oxidation film 2 and silicone oil 4 can be obtained. Here, as described above, since a silicone oil solution can be used as an impregnation liquid, each component in the silicone oil solution may be impregnated in the pores of the micro-arc oxidation film. However, due to the baking process, volatile components (for example, isopropanol solvent) can be volatilized and retained less in the pores or not retained in the pores at all. Thus, in addition to the substrate 1, the micro-arc oxidation film 2 and the silicone oil 4, the non-stick layer may also include solvents such as isopropanol and titanates and / or coupling agents (for example, silane coupling agents) as catalysts.

[0063] In order to further seal the micro-arc oxidation film 2 including the silicone oil 4 to improve the non-stickiness, a ceramic coating may be sprayed on the surface of the micro-arc oxidation film 2 for sealing. According to an exemplary embodiment, the ceramic coating may be a ceramic coating commonly used in the art, and therefore, may be prepared using a conventional formula of the prior art.

[0064] According to an example, the ceramic coating can be prepared by the following method: providing material A, material B and material C respectively, and mixing material A, material B and material C in sequence to obtain the ceramic coating.

[0065] Here, material A may include silane substances and silicone oil, material B may include silica sol and filler as essential components, optional pigments, wetting agents, thickeners and emulsifiers as unnecessary components and solvents, and material C may include organic acids as essential components, and optional pH buffers and catalysts (e.g., zirconium acetate) as unnecessary components.

[0066] In the A material, according to an exemplary embodiment, the silane substance is used to form polysiloxane during the formation of the ceramic coating, and therefore, the silane substance here may include a substance known in the art for polycondensation to form polysiloxane. According to an exemplary embodiment, the silane substance may include at least one of methyltrimethoxysilane, methyltriethoxysilane and dimethyldimethoxysilane, but is not limited thereto. In addition, in addition to the silane substance, the A material may also include tetraethyl orthosilicate that is polycondensed to form polysiloxane, and in this case, in the A material, the weight portion of the silane substance may be 80%-97%, and the weight portion of tetraethyl orthosilicate may be 3%-20%. In addition, the silicone oil may be the silicone oil included in the micro-arc oxidation film as described above, and may include the same type or different types of silicone oil as the silicone oil in the micro-arc oxidation film. To avoid redundancy, the silicone oil is not described in detail here, and the weight portion of the silicone oil in the A material may be 1%-5%.

[0067] Material B may necessarily include fillers and silica sol. The filler plays a role in increasing the wear resistance of the coating, etc. Therefore, the present invention does not limit the type of filler, and ordinary commonly used fillers can be selected, for example, at least one of mica powder, kaolin, montmorillonite, silicon carbide, alumina and silicon dioxide can be selected. In addition, silica sol is the main film-forming substance of ceramic coatings, which reacts with polysiloxane under acidic conditions to form a ceramic coating. Therefore, commercially available ordinary silica sol can be selected as the silica sol in material B of the present invention. For example, the silica sol can be Akzo Nobel 1050 (silica sol) or American Grace LUDIXAM-50.

[0068] The necessary components in the B material can be dispersed in a solvent. That is, the B material can also include a solvent. Here, the solvent can include deionized water, and in order to adjust the volatilization rate of the solvent during the coating drying process, the solvent can also include isopropanol. In addition, the ratio between isopropanol and water is unlimited, and the ratio between water and isopropanol can be selectively proportioned according to actual needs.

[0069] In the B material, in addition to the above-mentioned necessary components, one or more of a pigment, a wetting agent, a thickener and an emulsifier may be selectively included as an unnecessary component. Here, the pigment is mainly used to give the coating different colors, so ordinary inorganic pigments can be selected. Inorganic pigments have good temperature resistance and good safety, and inorganic pigments are preferably selected in the high temperature resistant field. According to an exemplary embodiment, at least one of carbon black, copper chrome black, titanium dioxide, iron oxide, etc. may be selected as a filler. In addition, during the preparation of the necessary components in the solvent, in order to provide the excellent properties of the material, at least one of a wetting agent, a thickener and an emulsifier may also be added to the material.

[0070] According to a specific example, the B material may include, by weight percent: 30wt%-48wt% of silica sol, 8wt%-13wt% of pigment, 8wt%-25wt% of filler, 0.2wt%-1wt% of wetting agent, 1wt%-3wt% of thickener, 3wt%-5wt% of emulsifier, and the balance is isopropyl alcohol and deionized water. However, exemplary embodiments are not limited thereto, and one or more of the unnecessary components may be omitted.

[0071] The C material is used as a strong acid catalyst, and may include an organic acid as an essential component, and an optional pH buffer and a catalyst (e.g., zirconium acetate) as an unnecessary component. Here, the organic acid is used to adjust the pH value of the silica sol in the subsequent process so that it can react with the A material in an acidic environment, and therefore, an organic acid commonly used in the art for ceramic coatings can be used. According to an exemplary embodiment, at least one of formic acid and acetic acid can be selected as an organic acid, and when both formic acid and acetic acid are included, the weight ratio between formic acid and acetic acid can be between 4:6 and 1:1. In addition, in the C material, a pH buffer and a catalyst may also be selectively included. Here, the pH buffer and the catalyst may be a pH buffer and a catalyst used in the process of preparing a strong acid catalyst for ceramic coatings known in the art, for example, the pH buffer may be a weak acid such as boric acid, and the catalyst is used to accelerate the reaction speed of the sol-gel, and may be zirconium acetate, etc. However, the exemplary embodiment is not limited to the types of pH buffers and catalysts, and suitable pH buffers and catalysts may be omitted or appropriately selected based on the prior art.

[0072] According to an exemplary embodiment, the C material may include 80-97 parts by weight of a mixture of formic acid and acetic acid, 1-2 parts by weight of a boric acid pH buffer, and 0.5 parts by weight of a zirconium acetate catalyst.

[0073] After providing the above-mentioned materials, a mixing step may be performed. Herein, the mixing step may include a first mixing step of mixing the B material with the C material and a second step of mixing the result of the first mixing step (ie, the first material described below) with the A material.

[0074] Specifically, 40-60 parts by weight of the B material can be mixed with 1-2 parts by weight of the C material, so that the pH of the mixture is adjusted to acidic (e.g., to less than or equal to 4) by using the acidity of the C material to obtain the first material. Since the B material includes a solid filler and an optional pigment, the B material can be added to a grinder and ground for 0.5h-2h before mixing or during the preparation of the C material, so that it is fully dispersed and ground to a particle size of less than or equal to 15 microns to obtain a uniformly dispersed slurry.

[0075] After the B material and the C material are mixed, the mixture may be tumbling dispersed for a predetermined time (eg, 0.5 h) so that the first material has a high degree of dispersion.

[0076] After obtaining the first material, material A may be added to the first material. Here, the weight ratio of the added amount of material A to material B may be in the range of (20-30):(40-60). After adding material A, material A and material B may be shaken evenly, and stirred at a speed of 120 rpm to 200 rpm for 6 to 8 hours, so that material A and material B undergo a sol-gel reaction in an acidic environment to form a ceramic coating.

[0077] After the ceramic coating is prepared, a spraying process can be performed. For example, the ceramic coating can be sprayed by air spraying. Here, the spraying of the ceramic coating does not limit the air spraying parameters. Here, the air spraying parameters are as follows: the spraying distance is 160mm; the air pressure is 0.3MPa; the flow rate is 8L / min. However, the exemplary embodiment is not limited to this, and the parameters of the air spraying can be adaptively adjusted according to the specific process, and those skilled in the art can also use other methods of forming layers to form a sealing layer using the ceramic coating conceived by the present invention.

[0078] After spraying, the resultant may be sintered at a temperature of 260° C. to 280° C. for 3 minutes to 10 minutes to form a sealing layer with a thickness of 3 micrometers to 15 micrometers.

[0079] Through the detailed description in combination with the exemplary embodiments above, the non-stick utensil including the non-stick layer conceived by the present invention includes a micro-arc oxidation film and silicone oil. Therefore, it maintains a long-lasting non-stick effect while having the advantages of wear resistance and corrosion resistance of the micro-arc oxidation film.

[0080] Hereinafter, the beneficial effects of the inventive concept will be described in conjunction with specific examples.

[0081] Example 1

[0082] S1: Provide an aluminum cookware base;

[0083] S2: 8g / L sodium silicate, 4g / L sodium hydroxide and 1g / L sodium fluoride were used to prepare an alkaline bath solution. In the constant voltage mode of 400V, the pulse frequency was 600Hz, the duty cycle was 10%, the micro-arc oxidation time was 20min, and the micro-arc oxidation film thickness was 15 microns;

[0084] S3: preparing a solution of hydroxy silicone oil with a molecular weight of 3000 and isopropanol in a mass ratio of 1:2;

[0085] S4: The micro-arc oxidation film with a film thickness of 15 μm was completely immersed in the silicone oil solution for 2 hours; thereafter, it was taken out, wiped dry, and baked at a temperature of 300° C. for 10 minutes.

[0086] Through the above method, the non-stick cookware of Example 1 is obtained.

[0087] Example 2

[0088] The difference from Example 1 is that in step S2, the micro-arc oxidation time is 35 minutes and the thickness of the micro-arc oxidation film is 25 microns.

[0089] Example 3

[0090] The difference from Example 1 is that in step S2, the micro-arc oxidation time is 50 minutes and the thickness of the micro-arc oxidation film is 33 microns.

[0091] Example 4

[0092] The difference from Example 1 is that in step S2, the micro-arc oxidation time is 60 minutes and the thickness of the micro-arc oxidation film is 40 microns.

[0093] Example 5

[0094] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 20 wt % of hydroxy silicone oil with a molecular weight of 800, 60 wt % of hydroxy silicone oil with a molecular weight of 3000 and 20 wt % of hydroxy silicone oil with a molecular weight of 12000.

[0095] Example 6

[0096] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 20 wt % of hydroxy silicone oil with a molecular weight of 1000, 50 wt % of hydroxy silicone oil with a molecular weight of 4000 and 30 wt % of hydroxy silicone oil with a molecular weight of 12000.

[0097] Example 7

[0098] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 30 wt % of hydroxy silicone oil with a molecular weight of 800, 50 wt % of hydroxy silicone oil with a molecular weight of 3000 and 20 wt % of hydroxy silicone oil with a molecular weight of 30000.

[0099] Example 8

[0100] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 30 wt % of hydroxy silicone oil with a molecular weight of 500, 50 wt % of hydroxy silicone oil with a molecular weight of 4500 and 20 wt % of hydroxy silicone oil with a molecular weight of 28000.

[0101] Example 9

[0102] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 30 wt % of hydroxy silicone oil with a molecular weight of 800, 40 wt % of hydroxy silicone oil with a molecular weight of 3000 and 30 wt % of hydroxy silicone oil with a molecular weight of 12000.

[0103] Example 10

[0104] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 30 wt % of hydroxy silicone oil with a molecular weight of 1000, 50 wt % of hydroxy silicone oil with a molecular weight of 5000 and 20 wt % of hydroxy silicone oil with a molecular weight of 15000.

[0105] Embodiment 11

[0106] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 20 wt % of hydroxy silicone oil with a molecular weight of 800, 60 wt % of hydroxy silicone oil with a molecular weight of 3000 and 20 wt % of hydroxy silicone oil with a molecular weight of 23000.

[0107] Example 12

[0108] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 20 wt % of hydroxy silicone oil with a molecular weight of 500, 60 wt % of hydroxy silicone oil with a molecular weight of 6000 and 20 wt % of hydroxy silicone oil with a molecular weight of 20000.

[0109] Embodiment 13

[0110] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 25 wt % of hydroxy silicone oil with a molecular weight of 800, 50 wt % of hydroxy silicone oil with a molecular weight of 3000 and 25 wt % of hydroxy silicone oil with a molecular weight of 25000.

[0111] Embodiment 14

[0112] The difference from Example 1 is that the hydroxy silicone oil is replaced by a silicone oil mixture consisting of 25 wt % of hydroxy silicone oil with a molecular weight of 1000, 50 wt % of hydroxy silicone oil with a molecular weight of 3000 and 25 wt % of hydroxy silicone oil with a molecular weight of 18000.

[0113] Embodiment 15

[0114] The difference from Example 1 is that it also includes a sealing layer formed by ceramic coating.

[0115] Ceramic coatings are formed by the following methods:

[0116] a: By weight, 80% of methyltrimethoxysilane, 20% of ethyl orthosilicate and 3% of hydroxy silicone oil with a molecular weight of 3000 are mixed and stirred uniformly to obtain a silane composition of component A;

[0117] b: 30wt% of Akzo Nobel 1050 (silica sol), 8wt% of titanium dioxide (pigment), 25wt% of kaolin (filler), 3wt% of Tween-80 (emulsifier), 1wt% of water-based modified bentonite (thickener), 0.3wt% of polyoxyethylene ether TRITON X-100 (wetting agent), 20wt% of isopropanol and the balance of deionized water were mixed evenly, then added to a grinder and ground for 2h, fully dispersed and ground to a particle size of no more than 15 microns, to obtain component B slurry;

[0118] c: 48 parts by weight of formic acid, 48 parts by weight of acetic acid, 1 part by weight of boric acid (buffer), and 0.5 parts by weight of zirconium acetate (catalyst) are uniformly mixed to obtain component C, a strongly acidic catalyst;

[0119] d: The above three components are mixed in order according to the weight ratio of A:B:C=22:40:1, and rolled to mature to obtain the ceramic coating. The mixing order and the aging method are as follows: first, 40 parts by weight of component B and 1 part by weight of component C are mixed evenly, and the pH is adjusted to 4 by component C, and the mixture is rolled and dispersed for 0.5 hours, and then 22 parts by weight of component A are added and shaken evenly, and the reaction is stirred at a speed of 200 rpm for 8 hours to obtain the desired ceramic coating;

[0120] The ceramic coating was sprayed by air spraying; the air spraying parameters were as follows: spraying distance was 160 mm; air pressure was 0.3 MPa; flow rate was 8 L / min.

[0121] After spraying, the film was sintered at 260°C for 3 minutes to form a sealing layer with a thickness of 3 microns.

[0122] Example 16

[0123] The difference from Example 15 is that a sealing layer with a thickness of 8 microns is formed.

[0124] Embodiment 17

[0125] The difference from Example 15 is that a sealing layer with a thickness of 15 μm is formed.

[0126] Embodiment 18

[0127] The difference from Example 1 is that the substrate has a double-layer structure of iron and magnesium stacked from bottom to top.

[0128] Embodiment 19

[0129] The difference from Example 1 is that in step S3, hydroxy silicone oil with a molecular weight of 800 is prepared, and in step S4, the micro-arc oxidation film with a film thickness of 15 μm is completely immersed in the silicone oil.

[0130] Embodiment 20

[0131] The difference from Example 1 is that in step S3, a silicone oil mixture consisting of 30wt% of hydroxy silicone oil with a molecular weight of 1000, 50wt% of hydroxy silicone oil with a molecular weight of 5000 and 20wt% of hydroxy silicone oil with a molecular weight of 15000 is prepared (i.e., excluding isopropanol solvent), and in step S4, the micro-arc oxidation film is completely immersed in the silicone oil mixture.

[0132] Embodiment 21

[0133] The difference from Example 1 is that in step S3, the solution further includes titanate with a mass fraction of 0.1%.

[0134] Embodiment 22

[0135] The difference from Example 1 is that in step S3, the solution further includes 0.2% by mass of titanate.

[0136] Embodiment 23

[0137] The difference from Example 1 is that in step S3, the solution further includes 0.3% by mass of titanate.

[0138] Embodiment 24

[0139] The difference from Example 1 is that in step S3, the solution further includes a silane coupling agent with a mass fraction of 0.1%.

[0140] Embodiment 25

[0141] The difference from Example 1 is that in step S3, the solution further includes a silane coupling agent with a mass fraction of 0.2%.

[0142] Embodiment 26

[0143] The difference from Example 1 is that in step S3, the solution further includes a silane coupling agent with a mass fraction of 0.3%.

[0144] Comparative Example 1

[0145] The difference from Example 1 is that only steps S1 and S2 are included, but steps S3 and S4 are not included.

[0146] Comparative Example 2

[0147] The difference from Example 1 is that step S3 is not included, and edible soybean oil is used to replace silicone oil in step S4.

[0148] Comparative Example 3

[0149] The difference from Example 1 is that step S4 does not include a baking operation.

[0150] Comparative Example 4

[0151] The difference from Example 1 is that in step S2, the micro-arc oxidation time is 10 minutes and the thickness of the micro-arc oxidation film is 10 microns.

[0152] Comparative Example 5

[0153] The difference from Example 1 is that in step S2, the micro-arc oxidation time is 80 minutes and the thickness of the micro-arc oxidation film is 60 microns.

[0154] The non-stick properties of the non-stick cookware of the above-mentioned Examples 1-26 and Comparative Examples 1-5 were tested, and the test results are shown in the following table.

[0155]

[0156]

[0157] Performance index test

[0158] The above-obtained cookware was subjected to a performance test, and the specific performance test method is as follows:

[0159] (1) Long-lasting non-stick test method: refer to 4.2.1 Fried egg non-stick test in GB_T 32095.2-2015. The unit is the number of times. The higher the number, the longer the life. The non-stick result is evaluated once every 1000 times, and the number of times when the non-stickiness reaches Level III is recorded.

[0160] (2) Plane wear resistance test method: GB_T 32095.2-2015 4.3.1 Plane wear resistance test, use 3M7447 scouring pad, apply a force of 15N, the frequency is 33 times / minute, and the scouring pad is replaced every 500 times.

[0161] By comparing and analyzing the embodiments 1-26 and comparative examples 1-5 of the present invention, it is not difficult to find that: the conventional ceramic coating of the existing micro-arc oxidation film in comparative example 1 has a long-lasting non-stickiness of no more than 500 times; in comparative example 2, edible soybean oil is used instead of silicone oil, so the long-lasting non-stickiness is relatively low; comparative example 3 does not include a baking operation, so the release rate of silicone oil increases, resulting in a decrease in long-lasting non-stickiness; comparative example 4 has a short micro-arc oxidation time, resulting in a thin film, which reduces the porosity and reduces the amount of silicone oil filled; comparative example 5 has a long micro-arc oxidation time, resulting in a thicker film, which increases the process cost and does not significantly improve the non-stickiness. In contrast, the long-lasting non-stickiness of the non-stick cookware according to the present invention is 8000-25000 times.

[0162] Although one or more embodiments of the present invention have been described with reference to the drawings, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the invention as defined by the claims.

Claims

1. A non-stick layer, characterized in that: The non-stick layer comprises: A micro-arc oxidation film is formed by a metal material using a micro-arc oxidation process, wherein the micro-arc oxidation film has a plurality of pores; Silicone oil fills at least the surface pores of the micro-arc oxidation film.

2. The non-stick layer according to claim 1, characterized in that The silicone oil is selected from at least one of methyl silicone oil, dimethyl silicone oil, hydroxy silicone oil, hydrogen-containing silicone oil and polyether-modified silicone oil.

3. The non-stick layer according to claim 1, characterized in that In terms of weight percentage, the silicone oil includes 20%-30% of low molecular weight silicone oil, 40%-60% of medium molecular weight silicone oil, and 20%-30% of high molecular weight silicone oil. Among them, the molecular weight of low molecular weight silicone oil is between 500-1000, the molecular weight of medium molecular weight silicone oil is between 3000-6000, and the molecular weight of high molecular weight silicone oil is between 12000-30000.

4. The non-stick layer according to claim 1, characterized in that The non-stick layer further comprises a sealing layer located on the micro-arc oxidation film, and the sealing layer is formed by using ceramic coating.

5. The non-stick layer according to claim 4, characterized in that The thickness of the sealing layer is in the range of 3 micrometers to 15 micrometers.

6. The non-stick layer according to claim 1, characterized in that The metal material includes at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, titanium and titanium alloy.

7. A method for preparing the non-stick layer according to any one of claims 1 to 6, characterized in that: The method comprises: A micro-arc oxidation film is formed on a substrate by using a micro-arc oxidation method; The micro-arc oxidation film is immersed in silicone oil or silicone oil solution, so that the silicone oil fills at least the surface pores of the micro-arc oxidation film.

8. The method according to claim 7, characterized in that In the immersion step, the micro-arc oxidation film immersed in the silicone oil is ultrasonically treated using ultrasonic waves.

9. The method according to claim 7, characterized in that After the dipping step, a sealing layer is formed on the micro-arc oxidation film using a ceramic coating.

10. A non-stick utensil, characterized in that: The non-stick utensil comprises: matrix; The non-stick layer according to any one of claims 1 to 6, located on a substrate, wherein the thickness of the micro-arc oxidation film is in the range of 14 microns to 40 microns.